2015
DOI: 10.1111/1759-3441.12099
|View full text |Cite
|
Sign up to set email alerts
|

On the International Trade and Economic Growth Nexus in New Zealand

Abstract: This study examines the effects of international trade and investment on output and tests the Granger‐causal nexus among trade, investment and economic growth in New Zealand for the period 1954–2007. The results provide consistent support for the long‐run effects of trade and investment on output. The optimal single‐equation and the vector autoregression‐based system estimates of the model consistently suggest positive and significant long‐run effects of exports and investment on output. The effects of imports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Success for these small firms stemmed from higher rates of R&D expenditure and multimarket exporting through company‐owned channels in distant markets. Singh (2015) notes a positive and significant long‐run relationship between exports, investment and economic growth in New Zealand. He emphasises that both the promotion of exports and increasing investments are crucial for fostering a higher level of output and economic growth in New Zealand.…”
Section: Global and New Zealand Evidence: The Literaturementioning
confidence: 99%
“…Success for these small firms stemmed from higher rates of R&D expenditure and multimarket exporting through company‐owned channels in distant markets. Singh (2015) notes a positive and significant long‐run relationship between exports, investment and economic growth in New Zealand. He emphasises that both the promotion of exports and increasing investments are crucial for fostering a higher level of output and economic growth in New Zealand.…”
Section: Global and New Zealand Evidence: The Literaturementioning
confidence: 99%
“…The nexus between economic growth and trade has received substantial attention in both theoretical and empirical literature in recent years. Several studies have demonstrated that trade promotes economic growth through favorable impacts on investment [ [22] , [23] , [24] , [25] ]. Trade is often associated with economic growth [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The economic integration of countries also relies on international trade and remittance from emigrants (Singh, 2015). First, international trade is a key factor to achieve rapid economic growth, especially for the least developed countries (LDC), since it can bring innovation and advance technology diffusion in the host country (Zheng & Walsh, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%